The asymptotic of the distribution of the maxima of the nonidentically distributed random variables - Arvydas Jokimaitis (Lietuvos Matematikos Rinkinys)
In this paper the nonuniform estimate for the distribution of the maxima of the nonidentically distributed independent random variables is obtained.